PENGARUH BEBAN PAJAK, TUNNELING INCENTIVE, DAN UKURAN PERUSAHAAN TERHADAP KEPUTUSAN PERUSAHAAN DALAM MELAKUKAN TRANSFER PRICING (Studi Empiris Pada Perusahaan Multinasional Yang Listing Di Bursa Efek Indonesia Tahun 2013-2017) - Siti Khusnul Khotimah (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of tax expense, tunnelingincentive and firm size to transfer pricing. This research is qualitative. Population in this research is multinational company subsector that listed in BEI during period of 2013 until 2017. The sample in this study was determined based on purposive sampling which resulted 23 samples of company. The type of data used is secondary data obtained from www.idx.co.id. Data analysis technique used is multiple linear regression analysis. The result of multiple regression test shows that the tax expense, tunneling incentive and firm size simultaneously affect the transfer pricing and the three independent variables influence 16,1% to the dependent variable while the rest is influenced by other factors outside the research variables. Partially, tax expense have a negatively effect on transfer pricing with t count equal to -2,020 and significance level 0,047, tunneling incentive has no effect on transfer pricing with t count smaller than t table that is equal to 0.064<1,658697 and and firm size negatively affect transfer pricing with t count equal to -4.727 and significance level 0.000.